Career Success View Retrospective from a Traditional Career to an Unlimited Career - Brian Soke; Arthur Smith; Lingka Lingka (Lembaga Riset Ilmiah, 2022)
This research is to see how career problems are increasingly changing the nature of careers and causing the emergence of a more autonomous and independent career without boundaries. Generally in various forms of careers without limit is mobility. Individuals who move psychologically and physically begin to manage their careers in terms of their pursuits. In such a caIn such environment, the nature of career success has also changed. A career becomes an important and subjective thing that is only emphasized more than objective career success because individuals themselves meaningfully define and assess their career success by referring to the standards, needs, and values ​​that they set themselves in an unstable environment. With the transmission of individual career responsibilities, it is necessary to develop competencies to find out why, know whose competencies, and know-how competencies emerge to survive and be successful. This study reviews the theoretical background of careers and the concept of a new career as a career without boundaries, in a constantly changing environment where it is impossible to be successful unless acquiring new competencies and methods of survival. New approaches to career success and the main reasons for emphasizing the development of subjective career success will also be examined